Local Radio Broadcasting System in Andalusia: a Way of Citizen Participation - Gabilondo García del Barco, Victoria (Historia y Comunicación Social, 2014)
First established more than 30 thirty years ago, the sector of local radio broadcasters in Andalusia is one of the key networks in the regional public media scene. This study aims to legitimize, show and promote a deeper knowledge of the public radio network, by historically tracing the growth and current state of LRB in Andalusia. This research work (attached to the University of Malaga) is part of the R&D&I Programme “CSO 2011 – 29195”, by the Department of Finance and Competitiveness.